Frequency of Perinatal Depression in Pregnant Women Utilizing Edinburgh Postnatal Depression Scale - Nilofar Mustafa, Qurutulain Mushtaq, Rehana Kanwal, Humaira Tabassum, Qudsia Nawaz, Samina Rehan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of perinatal depression in pregnant women utilizing Edinburgh Postnatal depression scale (EPDS). Study Design: Cross-sectional study Settings: Out-patient Department of Obstetrics and Gynecology, Combined Military hospital, Lahore. Duration of study: 1st November 2018 to 30th April 2019 Total 254 patients were selected. Patients were questioned according to EPDS scale and information recorded on prescribed form. Data was stratified for age, parity, gestational age, education level, and income group. Pregnant women with an EPDS score of ≥9 were considered to be suffering with depression. Results: In this present study a total of 254 women were interviewed for perinatal depression. The mean age of the patients was 27.64 ±8.89 years with minimum and maximum ages of 20 years and 34 years respectively. The mean gestational age of the patients was 38.31±2.16 weeks with a minimum and maximum gestational age of 37.40 and 40.02 respectively. In the study a total of 254 women were assessed for perinatal depression. 19.2% of women were found to be suffering from perinatal depression. Conclusion: “The results of our study demonstrate that, both antepartum and postpartum depression, in pregnant women are significantly prevalent.” Keywords: “Edinburgh Postnatal depression scale (EPDS), perinatal depression, low-income countries (LIC), high-income countries (HIC).”